2001
DOI: 10.1007/s15010-001-1173-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disseminated Encephalomyelitis (ADEM) Due to Mycoplasma pneumoniae Infection in an Adolescent

Abstract: A 17-year-old boy presented with a severe form of an acute disseminated encephalomyelitis (ADEM) with hemiparesis and coma after initial symptoms of a flu-like febrile infection 1 week previously. Titers against Mycoplasma pneumoniae were significantly increased in serum and cerebrospinal fluid (CSF). Detection of M. pneumoniae was achieved in the initial CSF sample using M. pneumoniae-specific PCR. The patient improved significantly on antimicrobial therapy with erythromycin and immunosupressive therapy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 7 publications
2
29
0
9
Order By: Relevance
“…M. pneumoniae RNA can be detected in brain tissue by nucleic acid hybridization (8), and the presence of the organism was demonstrated in cerebrospinal fl uid by PCR (1,(9)(10)(11)(12) and by culture (3,12). As shown in our case, the microbial antigens can be immunohistochemically detected in histopathologically involved areas of the CNS, both in brain biopsy specimens and at autopsy.…”
supporting
confidence: 52%
“…M. pneumoniae RNA can be detected in brain tissue by nucleic acid hybridization (8), and the presence of the organism was demonstrated in cerebrospinal fl uid by PCR (1,(9)(10)(11)(12) and by culture (3,12). As shown in our case, the microbial antigens can be immunohistochemically detected in histopathologically involved areas of the CNS, both in brain biopsy specimens and at autopsy.…”
supporting
confidence: 52%
“…Because of its diverse distribution of affected areas, an indirect mechanism has been postulated, namely, immune complexmediated vasculopathy [Behan et al, 1986;Guleria et al, 2005;Gupta et al, 2009]. On the other hand, recent studies on patients with acute disseminated encephalomyelitis have demonstrated the presence of M. pneumoniae genome in the cerebrospinal fluid [Matsumoto et al, 2009;Riedel et al, 2001;Yiş et al, 2008], or the presence of M. pneumoniae antigens inside the macrophages in the brain tissue [Stamm et al, 2008]. Thus it is highly possible that a direct mechanism, namely, vasculitis as a consequence of cytokine activation by M. pneumoniae, is responsible for some instances of acute disseminated encephalomyelitis.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%
“…14 However, to our knowledge only two other case reports have described ADEM due to bacterial meningitis, and none was associated with Hib. 14,19 Here we have shown, for the first time, to our knowledge, that ADEM can occur in association with acute Hib meningitis. In the setting of an acute bacterial meningitis, complicated with depression of consciousness and focal neurological deficits, the hypothesis of ADEM must be considered and should prompt further neurological investigation.…”
Section: Discussionmentioning
confidence: 56%